The Effect of Capital Structure and Sales Growth on Company Profitability and Value in theÂ Cosmetics Manufacturing and Household Needs ManufacturingÂ Companies - Ni Putu Erlin Pramesti; Putu Ngurah Suyatna Yasa; Ni Luh Anik Puspa Ningsih (Jurnal Ekonomi dan Bisnis Jagaditha, 2021)
Company value is very important for a company, because the company's value reflects the company's performance which will be associated with stock prices, where the higher the stock price, the higher the value of the company. With a high company value will give a good signal to investors that the company's financial performance is increasing. This study aims to determine the effect of capital structure and sales growth on profitability and firm value. The population in this study is cosmetics and household needs manufacturing companies listed on the IDX. Determination of the sample is done by a purposive sampling method of judgment sampling type and based on predetermined criteria; the number of samples is 5 companies manufacturing cosmetics sub-sectors and household needs. This study uses secondary data obtained from the Indonesia Stock Exchange in 2008-2018. Testing the hypothesis of the study used descriptive statistical test techniques and path analysis test with SPSS (Statistical Product and Service Solutions) application tools. The results showed that: 1) Capital structure has a positive and significant effect on profitability 2) Sales growth has a negative and not significant effect on profitability 3) Capital structure has a positive and significant effect on firm value 4) Sales growth has a positive and significant effect on firm value 5) profitability has a positive and significant effect on firm value 6) Capital structure is able to influence the value of the company through profitability 7) Sales growth is not able to affect the value of the company through profitability.